Dampak Korupsi, Kebebasan Ekonomi, Tata Kelola, Inflasi, dan Pertumbuhan Ekonomi terhadap Profitabilitas Bank: Studi Kasus pada kawasan ASEAN - Styawati, Diyah Ajeng; Meylianingrum, Kurniawati Meylianingrum (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
Sharia banking in the ASEAN region is increasingly needed to run a country's economy. This research collected samples from Sharia banking in the ASEAN region. The data taken was obtained from each banking website used as a sample. The reason for choosing Sharia banking from various countries in ASEAN is that it allows them to represent the diversity of economic conditions, governance, and culture in the region. Therefore, the author wants to know whether there is a significant influence if the analysis is aimed at Sharia banking companies in the ASEAN region. The method used in this research is multiple linear regression using a quantitative approach. This research found that corruption and inflation had a significant positive effect on bank profitability, and economic growth significantly negatively affected bank profitability. Meanwhile, the variables of financial freedom and governance do not substantially impact bank profitability.